ANALISIS EFISIENSI DAN FAKTOR-FAKTOR YANG BERPENGARH TERHADAP HASIL PRODUKSI USAHATANI PADI ORGANIK DI PROVINSI JAWA BARAT (Suatu kasus di Kelompok Tani Sari Alam Desa Cibatu Kabupaten Sukabumi dan Kelompok Tani Terlaksana Kelurahan Sukakarya Kota Sukabumi) - Romy Sudiawan; Euis Dasipah; Dety Sukmawati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
This study aims to analyze what production factors affect organic rice production and how efficient the use of these production factors is in the Sari Alam Farmer Group, Cibatu Village, Sukabumi Regency and the Implemented Farmer Group, Sukakarya Village, Sukabumi City. The research area method was carried out purposively (deliberately). The number of samples was 40 farmers from the Sari Alam Farmer Group, Cibatu Village, Cikembar District, Sukabumi Regency and 40 farmers from the Implemented Farmer Group, Sukakarya Village, Warudoyong District, Sukabumi City, the data used was for one planting season. The first hypothesis is analyzed by multiple regression analysis, the second hypothesis includes technical efficiency, price efficiency and economic efficiency using the frontier function. The results of the analysis of the two statistical test sample areas showed that simultaneously the independent variables consisting of land area, seeds, compost, liquid organic fertilizer and labor had a significant effect on the dependent variable, namely organic rice production. The classical assumption test shows that the research data is normally distributed, free of multicollinearity symptoms and there is no strong correlation between independent variables. The results of organic rice farming calculations show that in the Sari Alam Farmer's Group technical efficiency (ET) is 0.997, price efficiency (EH) is 7.266 and economic efficiency (EE) is 7.204 and in Implemented Farmers Group technical efficiency (ET) is 0.998, price efficiency ( EH) of 5.960 and economic efficiency (EE) of 5.948. The economic value in both farmer groups is more than 1, meaning that organic rice farming activities in both groups are very efficient.